(untitled) (Journal of Surgical Sciences, 2020)
Bile Duct Injury (BDI) is an unfortunate complication of cholecystectomy, if not treated properly may result in the death of the patient due to biliary peritonitis and sepsis or may convert an otherwise healthy young person with a biliary cripple with benign biliary stricture (BBS), cholangitis, secondary biliary cirrhosis, portal hypertension & liver failure. A BDI, even after repair, adversely affects the quality of life and can be a financial disaster for the patient and a legal one for the surgeon. As BDI is associated with health & financial disaster, more attention needs to be paid both to prevent and to recognize early such injury. After recognition the patient should be referred to a surgeon experienced in the management of such injuries to avoid further complications. Journal of Surgical Sciences (2019) Vol. 23 (1) : 33-36